Regional Economic Outlook, November 2007 : Europe: Strengthening Financial Systems. (Regional Economic Outlook; November 2007, 2007)
Strong fundamentals should allow Europe to weather financial turbulence relatively well. Nonetheless, growth is set to ease in 2008 in nearly all countries. Policymakers will need to deal up front with the financial market turmoil, while implementing fiscal consolidation and structural reforms, including in the financial sector, to address vulnerabilities, raise medium-term growth prospects, and deliver on the promise of convergence for emerging Europe. Three analytical chapters discuss reforms to strengthen Europe's financial systems to allow advanced economies to benefit from innovation without incurring excessive risk and, in emerging economies, to manage rapid financial deepening and develop financial systems further.